Induction of secondary cytotoxic T lymphocytes by purified HLA-A and HLA-B antigens reconstituted into phospholipid vesicles. - Engelhard, V H (1978)
Mouse cytotoxic T lymphocytes were induced by culturing primed spleen cells with cells, membranes, or detergent-solubilized and dialyzed membranes from the human lymphoblastoid cell line JY. Cytotoxic T cells could also be induced by coculturing primed spleen cells with phospholipid vesicles containing purified HLA-A and -B antigens derived from JY cells. The induction of killer cells by all subcellular fractions demonstrated an optimal response as a function of the amount of material added and, in the case of HLA-containing liposomes, this optimum was dependent upon the density of the HLA molecules in the liposomes. In addition, the maximal level of cytotoxicity elicited was also dependent upon this density. Finally, the cytotoxic cells demonstrated specificity as judged by a lower level of lysis on an HLA-unrelated lymphoblastoid cell line than on the appropriate target, JY. These results suggest that major histocompatibility antigens alone are sufficient for the induction of a secondary cytotoxic T lymphocyte response. It is proposed that this system may be useful in defining possible sites on the HLA molecule recognized by cytolytic T lymphocytes.